A bibliometric analysis of the clinical development of drugs in Norway for the year 2000. (13th March 2012) - Hole, Ola P.; Winther, Finn O.; Cederkvist, Henrik R.; Nitter‐Hauge, Sigurd
Abstract Purpose: Bibliometric analysis of publications was used to investigate the research output relating to the development of drugs in Norway and to evaluate the impact of Norwegian involvement in this research. Material and methods: One hundred and nine articles published between 2002 and 2008 were analysed. Bibliometric methods used were as follows: information on peer review, impact factor (IF), the Science Citation Index (SCI) and the representation of Norwegians in the list of authors. Results: All publications were in journals with peer review or in publications with corresponding evaluation. Industrial support, international research cooperation and drug development in phases I, II and III seem to promote publication in journals with high IF and a high SCI. In 63% of the international project articles, the Norwegian contributors were not represented in the list of authors. Conclusion: In addition to a scientific standard secured by referees, three probably independent factors – industrial support, international cooperation and early phases of the research (phases I, II and III) – seem to promote publications in journals with high IF and a high SCI. A more active Norwegian contribution to the research should be encouraged.